2010
DOI: 10.3378/027.082.0402
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Local Evolution of African mtDNA Haplogroups in Tunisian Berber Populations

Abstract: Our objective is to highlight the age of sub-Saharan gene flows in North Africa and particularly in Tunisia. Therefore we analyzed in a broad phylogeographic context sub-Saharan mtDNA haplogroups of Tunisian Berber populations considered representative of ancient settlement. More than 2,000 sequences were collected from the literature, and networks were constructed. The results show that the most ancient haplogroup is L3*, which would have been introduced to North Africa from eastern sub-Saharan populations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It is bounded by the Sahara desert to the South, by the Mediterranean Sea on the North and East, and by Algeria to the West. Mitochondrial DNA evidence supports the idea that Tunisia was occupied more than 20,000 YBP by a group originating from sub-Saharan Africa (Frigi et al, 2010;Soares et al, 2012). By 15,000 YBP the Mechto€ ıdes, also known as Ibero-Maurisans, appear (Bedoui, 2002).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It is bounded by the Sahara desert to the South, by the Mediterranean Sea on the North and East, and by Algeria to the West. Mitochondrial DNA evidence supports the idea that Tunisia was occupied more than 20,000 YBP by a group originating from sub-Saharan Africa (Frigi et al, 2010;Soares et al, 2012). By 15,000 YBP the Mechto€ ıdes, also known as Ibero-Maurisans, appear (Bedoui, 2002).…”
mentioning
confidence: 71%
“…There are those who say that a civilization radiated to North Africa 40,000 years ago built by the Aterian, after which North Africa was depopulated (see the introduction to Rando et al, 1998). Indeed, uniparental genetic data support the arrival of sub-Saharans around 20,000 years ago according to Frigi et al (2010). Other studies show that the introduction of sub-Saharan mtDNA lineages in North Africa is older than 30,000 YBP (Soares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This was marked by the invasion of Bedouin tribes (Banu Hilal), followed by the Arabization and Islamization of many Berber populations. Even so, previous studies on Tunisian populations displayed the mosaic structure of the mitochondrial gene pool, which is characterized by an overall high frequency of Eurasian haplogroups (∼70%), followed by Sub‐Saharan L lineages (∼ 25%), and lesser frequencies of North African haplogroups U6 and M1 (5%) (Fadhlaoui‐Zid et al, ; Frigi et al, ; Kefi et al, ). However, of these mtDNA, only Fernandes et al () estimated the recent contribution of Near Eastern sublineages, i.e., K1a1, N1, T, J, R0a, U, and X, suggesting that they arrived around 2000 years ago, probably associated with Phoenician occupation.…”
Section: Introductionmentioning
confidence: 96%
“…Other studies revealed the arrival of some L sublineages in North Africa across the Sahel Belt during the Early Holocene at the beginning of the African Humid Period (11 000 years ago), particularly L1b and L3e5 which are commonly found in the Lake Chad Basin (Černý, Salas, Hájek, Žaloudková, & Brdička, ; Frigi et al, ; Hernández et al, ; Podgorná, Soares, Pereira, & Černý, ; Soares et al, ). Conversely, U6 and some L sublineages were introduced from northwest Africa into Iberia probably after the Younger Dryas period (Cerezo et al, ; Hernández et al, ; Podgorná et al, ; Secher et al, ; Soares et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation